Design theory of earthquake-resilient prefabricated sinusoidal corrugated web beam-column joint. (1st November 2017) - Zhang, A.L.; Li, S.H.; Jiang, Z.Q.; Fang, H.; Dou, C.
Highlights: A new type earthquake-resilient PSCWJ is put forward. The mechanics mechanism and seismic design requirements of PSCWJ are introduced. The design theory of an earthquake-resilient PSCWJ is established. The rationality of the design theory of PSCWJ proposed in this study is verified. PSCWJ has good bearing behaviour, ductility, and earthquake resilience capacity. Abstract: Prefabricated steel structure systems have become a new trend in the development of steel structures. In particular, earthquake-resilient steel structures have become a hot issue in the field of structural seismic research. Based on the idea of damage control and a new kind of energy-saving, material-saving and environmentally friendly sinusoidal corrugated web, this paper put forward a new type of earthquake-resilient prefabricated sinusoidal corrugated web beam-column joint (PSCWJ). Then, its constitution, its mechanics mechanism and its seismic design requirements are introduced. After considering the influence of the bolt binding coefficient, the overall bending of the binding section and the overall instability of the flange cover plate, the design theory of the earthquake-resilient PSCWJ is established. Through 55 examples of PSCWJs, the rationality of the design theory proposed in this study is verified, and a reasonable value range of the middle bolt interval on the flange cover plate is determined. During the process of theoretical derivation, the influences of many design parameters are considered, such as the section parameters of the sinusoidal corrugated web beam and cantilever beam, the thickness of the flange cover plate, the material properties of the flange cover plate, the diameter of bolts, the middle bolt interval and the weaken rate of the cover plate. Research shows that the design theory proposed in this paper can predict the yield load of PSCWJ accurately and effectively control the ultimate bearing capacity of PSCWJ. The PSCWJ designed through this theory has good bearing behaviour and ductility, which can make sure the main members, such as the beam and the column, remain in an elastic range and meet the requirements of earthquake resilience.